Profit comparative of fisheries in East Aceh Regency, Indonesia - Mawardati, Mawardati; Jullimursyida, Jullimursyida (Universitas Malikussaleh, 2020)
This research was conducted from March to May 2018 in East Aceh District, Aceh Province, Indonesia. This study aims to analyze the differences between traditional milkfish and shrimp culture in East Aceh District, Aceh Province. The analytical method used is acquisition analysis and Independent Sample t-test analysis. The results showed a significant difference between milkfish and shrimp culture in East Aceh District, Aceh Province. Based on the results of the analysis, the average profit from shrimp culture is higher than milkfish culture. This demand exceeds market demand for exports. Thus the price of shrimp is still far higher than milkfish.Keywords: comparative; profit; shrimp; milkfish